IMMUNOHISTOCHEMICAL EXPRESSION OF CYCLIN D1 AND c-MYC PROTEINS IN INTRACRANIAL MENINGIOMA - Ribas, Carmen Austrália Paredes Marcondes (2022)
Background: Intracranial meningioma is the most frequent tumor of the central nervous system and immunohistochemical markers are important to aid in targeted therapy and prognosis. Objective: To evaluate the expression of cyclin D1 and c-MYC markers in intracranial meningiomas and to correlate it with the aggressiveness and recurrence of these tumors. Method: Retrospective, observational, cross-sectional study using data from the medical records of patients diagnosed with intracranial meningioma who were hospitalized and underwent surgical resection. Epidemiological, clinical and radiological data were collected and recorded. Immunohistochemistry for cyclin D1 and cMYC markers was performed on all samples. The data regarding the histological grade of the tumors were crossed with the result obtained by immunostaining. Results: 51 patients were included (72.5% women and 27.5% men) with a mean age of 53.5 years. Headache was the most common symptom and tumors located at the base of the skull accounted for 53% of cases. Grade I meningiomas were detected in 58.8%, grade II in 29.4% and grade III in 9.8%. Tumor recurrence was observed in two cases (3.9%) and disease-free patients corresponded to 49%. The mean follow-up time was 798 days (13-2267). Cyclin D1 was identified in 100% of meningiomas and the intensity of its expression was weak in 52.4% of grade I lesions, moderate in 50% of grade II tumors and strong in 100% of grade III tumors (p<0.001). c-MYC was identified in 17.7% (4.7% grade I, 66.7% grade II and 100% grade III) and its expression was weak in 50% in grade II and moderate in 100% in grade III (p<0.001). The presence of markers had no statistically significant relationship with patient outcomes. Conclusion: Cyclin D1 was expressed in all samples of meningiomas and the c-MYC was expressed in 18% of cases. The higher the histological grade, the more intense was the expression of the markers. There was no evidence of a relationship between the markers and tumor recurrence.